Alternative Dispute Resolution: Justice Without Trial - Gupta, Akshita (Trinity Law Review, 2021)
India having one of the largest democracy and widest Judicial system, it has often been  found that the courts in India have failed to show their competence in coming up with  a quick resolution. Even though the Constitution of India and the Apex court of India,  the Supreme Court, has given its consent and full support to the establishment and  execution of Alternative Dispute Resolution (ADR) protocols that are meant for  providing quick solutions to cases. But despite the presence of a statutory ADR system  in India, many cases like matrimonial and family disputes are still considered as  troublesome affairs taking enormous time to get any sort of satisfactory resolution as  quite often the ADR system’s presence and functioning remains hidden to the  appellants. The primary objective of this research paper is to concentrate on the  functioning and limitations of the ADR system, particularly in terms of providing  satisfactory resolution cases (including divorce, domestic violence, and child custody  cases).
Keywords: democracy; establishment; ADR; Dispute; divorce